2007
DOI: 10.1534/genetics.107.079715
|View full text |Cite
|
Sign up to set email alerts
|

tint Maps to Mouse Chromosome 6 and May Interact With a Notochordal Enhancer of Brachyury

Abstract: At the proximal part of mouse chromosome 17 there are three well-defined genes affecting the axis of the embryo and consequently tail length: Brachyury, Brachyury the second, and the t-complex tail interaction (T1, T2, and tct). The existence of T1 and tct in fact defines the classical ''t-complex'' that occupies 40 cM of mouse chromosome 17. Their relationship to each other and various unlinked interacting genes has been enigmatic. The tint gene was the first of the latter to be identified. We report here its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…This represents the so-called 'T-streak' promoter which directs expression only in the primitive streak and derivatives (Clements et al, 1996). Studies of the T promoter have revealed that the notochord-specific region is either trans or long-range cis-acting (Clements et al, 1996;Wu et al, 2007), which would complicate the ability to locate a causative mutation if it affected the notochord expression of T specifically. Our results imply that a mutation in the notochord-specific promoter/enhancer element of T could contribute to sacral agenesis along with urorectal anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…This represents the so-called 'T-streak' promoter which directs expression only in the primitive streak and derivatives (Clements et al, 1996). Studies of the T promoter have revealed that the notochord-specific region is either trans or long-range cis-acting (Clements et al, 1996;Wu et al, 2007), which would complicate the ability to locate a causative mutation if it affected the notochord expression of T specifically. Our results imply that a mutation in the notochord-specific promoter/enhancer element of T could contribute to sacral agenesis along with urorectal anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…NM RefSeq CNS variants within this area were identified using MGI and indexed by accession number and location (S1 Table). CNS polymorphisms were detected at i) T cell lymphoma invasion and metastasis 2 ( Tiam2 ), which distorts allele transmission and expression [48] and regulates neurite growth [49]; ii) NADPH oxidase 3 ( Nox3 ), which forms reactive oxygen species (ROS) by catalyzing electron transfer from NADPH to O 2 [50] and has been linked to T2DM in West Africans [51]; iii) zinc finger , DHHC domain containing 14 ( Zdhhc14 ), which is overexpressed in gastric tumours [52] and lymphoproliferation [53]; synaptojanin 2 ( Synj2 ), an important lipid phosphatase involved in vesicle recycling [54,55]; iv) fibronectin type III domain containing 1 ( Fndc1 ) involved with squamous and basal cell carcinomas [56]; v) brachury 2 ( T2 ), a t-complex gene critical to the development of the embryonic axis [57]; vi) phosphodiesterase 10A ( Pde10A ) which mediates intracellular signal transduction by hydrolyzing intracellular cAMP and cGMP concentrations [58], linked to bipolarity [59], the suppression of which is linked to diabetes and obesity [60] via thermoregulation [61]; vii) poly (A) binding protein , cytoplasmic 6 ( Pabpc6 ), which polyadenylates the tail of mRNA precursors [62]; viii) insulin-like growth factor 2 receptor ( Igf2r ); ix) adherens junction formation factor ( Afdn ), an Ca 2+ -independent target of Ras that helps create cell-cell adhesions [63]; x) hyaluronan synthase 1 ( Has1 ), which synthesizes hyaluronan (tissue homeostasis, provides compression resistance and lubricates tissues) in connective tissues and recruits lymphocytes in cancerous tissues [64]; and xi) an array of vomeronasal and zinc-finger genes (S1 Table).…”
Section: Resultsmentioning
confidence: 99%
“…The general basis of dispersive gene action–whether through genes with core physiological functions or those directly related to a given dispersed trait–is unclear [66]. Coding polymorphisms in the consensus Chr 17 area included those linked to cancer ( Fndc1 , Tiam2 , Zdhhc14 Has1 ) [48,52,56,64], growth and development ( Igf2r , Afdn , Tiam2 , T2 ) [49,57,63], immunology [53] or diabetes itself via the energetic electron transfer chain ( Tiam2 , Pde10A ) [50,51] or basal thermal metabolism [61]. Tiam2 modifies allele transmission and expression [48] in addition to its other roles, which could be a central modifier of the propensity to dispersive or stable physiological function.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the gene Brachyury (or “ T ,” for “tail”), which in mouse is part of the t -complex that spans 40 cM on chromosome 17 [79], did not occur until 1990; the gene was isolated by positional cloning [80] and found to be expressed in notochord and primitive-streak mesodermal cells [81]. Three years later, the Brachyury protein was classified as a novel sequence-specific transcription factor [82].…”
Section: The Role Of Brachyury In Notochord Evolution and Developmentmentioning
confidence: 99%